2011
DOI: 10.1002/jat.1614
|View full text |Cite
|
Sign up to set email alerts
|

Antigenotoxicity of artepillin C in vivo evaluated by the micronucleus and comet assays

Abstract: Artepillin C (3,5-diprenyl-p-coumaric acid), a major compound found in Brazilian green propolis and Baccharis dracunculifolia, shows anti-inflammatory, antibacterial, antiviral, antioxidant and antitumoral activities, among others. The aim of this study was to evaluate the genotoxic potential of artepillin C and its ability to prevent the chemically induced chromosome breakage or loss and the primary DNA damage using the micronucleus and comet assays in male Swiss mice, respectively. The animals were treated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Positive control compounds in micronucleus tests, other than comet assays, have also been used (de Azevedo Bentes Monteiro Neto et al , 2011; Malini et al , 2010). DXR was selected through being an effective genotoxic and mutagenic agent in in vivo and in vitro studies (Antunes and Takahashi, 1998; Takeuchi et al , 2008; Dutra et al , 2009; Tan and Porter, 2009; Ribeiro et al , 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Positive control compounds in micronucleus tests, other than comet assays, have also been used (de Azevedo Bentes Monteiro Neto et al , 2011; Malini et al , 2010). DXR was selected through being an effective genotoxic and mutagenic agent in in vivo and in vitro studies (Antunes and Takahashi, 1998; Takeuchi et al , 2008; Dutra et al , 2009; Tan and Porter, 2009; Ribeiro et al , 2010).…”
Section: Discussionmentioning
confidence: 99%
“…MMS causes predominantly methylation in nitrogens of purine rings, which can lead to the formation of apurinic sites (de Azevedo Bentes Monteiro Neto et al , 2011). Our results demonstrated that a single administration of MMS (50 mg/kg i.p.)…”
Section: Discussionmentioning
confidence: 99%
“…Considering that baccharin is not the only phytochemical present in propolis, the same group of Oliveira (2013) [201] and the scientific group of de Azevedo Bentes Monteiro (2011) [204] explored the protective activity of artepillin C (3, 5-diprenyl p-coumaric acid-), one of the major phenolic compounds found in Brazilian green propolis. De Azevedo Bentes Monteiro Neto and colleagues analyzed the antigenotoxicity of artepillin C against the damage produced by DXR and MMS in male Swiss mice using the micronucleus and comet assays.…”
Section: Natural Resinmentioning
confidence: 99%
“…The results showed that artepillin C itself was not genotoxic in the mouse comet extent assays. Artepillin C at the tested doses significantly reduced DNA damage extent in liver cells induced by MMS [62]. León-Mejía et al, evaluated genotoxic effects in a population exposed to coal residues from the open-cast mine "El Cerrejón".…”
Section: Recents Studies Using Comest Assaymentioning
confidence: 99%